Orange Juice and Yogurt Carrying Probiotic Bacillus coagulans GBI-30 6086: Impact of Intake on Wistar Male Rats Health Parameters and Gut Bacterial Diversity - Almada-Érix, Carine N.; Almada, Caroline N.; Cabral, Lucélia; Barros de Medeiros, Viviane Priscila; Roquetto, Aline R.; Santos-Junior, Valfredo A.; Fontes, Melline; Gonçalves, Any Elisa S. S.; dos Santos, Andrey; Lollo, Pablo C.; Magnani, Marciane; Sant’Ana, Anderson S. (Frontiers in Microbiology, 2021)
This study aimed to investigate the impact of the food matrix (orange juice and yogurt) on the effects of the spore-forming probiotic microorganism Bacillus coagulans GBI-30 6086 in health parameters and gastrointestinal tract (gut) bacterial diversity in Wistar male rats. Rats (n=48) were randomly distributed into six groups. The groups were Control (which received sterile distilled water), Juice (which received orange juice), Yogurt (which received yogurt), Probiotic Bacillus (which received B. coagulans GBI-30 6086 in distilled water), Probiotic Juice (which received orange juice with B. coagulans GBI-30 6086) and, Probiotic Yogurt (which received yogurt with B. coagulans GBI-30 6086). Each animal belonging to the different groups was treated for 21 days. The daily administration of probiotic juice or probiotic yogurt did not affect rats' food or body weight. Rats fed Probiotic Yogurt showed lower glucose and triglycerides levels (p < 0.05) in comparison to the control group (p ˂ 0.05), while no changes in these parameters were observed in rats fed Probiotic Juice. Rats fed Probiotic Yogurt showed higher gut bacterial diversity than the control group (p ˂ 0.05), and higher abundance (p ˂ 0.05) of Vibrionales, Enterobacteriales, Burkholderiales, Erysipelotrichales, and Bifidobacteriales compared to all other groups. No changes were observed in expression levels of antioxidant enzymes or heat shock protein 70 of rats fed probiotic yogurt or probiotic juice. Results reveal that consumption of yogurt containing B. coagulans GBI-30 6086 decreases triglycerides and glucose levels and positively impacts the gut bacterial ecology in healthy rats. These animal model findings indicate that the matrix also impacts the functionality of foods carrying spore-forming probiotics. Besides, this research indicates that yogurt is also a suitable food carrier of Bacillus coagulans GBI-30 6086